Benefits of Massage for Infants Aged 3 to 5 Months - N. Surtinah; Agung Suharto (Humanistic Network for Science and Technology (HNST), 2018)
This study discussed about the evaluation of massage influence on 3 to 5-months-old baby in Tawanganom, Magetan 2017. This research was analytical research by Quasy Experimental design in form of nonequivalent control group design with population of 20 babies who were massaged and not massaged. This study used sample of total population. Independent variable was massage for baby, while, dependent variable was baby’s weight by using ratio scale. The instrument of data collection used weight scale for baby in grams. Moreover, the statistical test that was used was independent sample T-Test. The results showed that the average of baby’s weight which the baby was massaged had a greater increase rather than non-massaged baby. The result of independent t-test was obtained p-value = 0.000 (<0.05). Thus, there was a significant influence of infant massage against baby’s weight gain of 3-5 months-old babies. Moreover, it could be concluded that there was a significant influence of infant massage against baby’s weight gain which the babies were 3-5 months old. Therefore, it was recommended for either families or mothers to massage their own baby, thus, their baby’s growth could be optimal. Keywords: Infant massage, Baby’s weight